2018
DOI: 10.1186/s13601-018-0214-y
|View full text |Cite
|
Sign up to set email alerts
|

Early nonreactivity in the conjunctival provocation test predicts beneficial outcome of sublingual immunotherapy

Abstract: BackgroundClinical practice needs a common parameter that can provide an early, reliable estimation of the outcome of sublingual immunotherapy (SLIT) in an upcoming pollen season. We investigated whether the conjunctival provocation test (CPT) can predict the beneficial outcome of SLIT in patients with allergic rhinoconjunctivitis after 4 weeks of treatment.MethodsWe conducted two separate prospective, randomized, double-blind, placebo-controlled, multicenter trials. Adults 18–75 years of age received placebo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…It is noteworthy that the CPT's efficacy results were consistent with the patient's subjective evaluations in their diary. Furthermore, it has been reported that early nonreactivity in a CPT reportedly predicts a positive outcome in AIT 44,45 . Secondly, the study took place outside the birch pollen season, which doubtless reduced interference with the results of the CPT and with safety measurements of reactions to the product's administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that the CPT's efficacy results were consistent with the patient's subjective evaluations in their diary. Furthermore, it has been reported that early nonreactivity in a CPT reportedly predicts a positive outcome in AIT 44,45 . Secondly, the study took place outside the birch pollen season, which doubtless reduced interference with the results of the CPT and with safety measurements of reactions to the product's administration.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that early nonreactivity in a CPT reportedly predicts a positive outcome in AIT. 44,45 Secondly, the study took place outside the birch pollen season, which doubtless reduced interference with the results of the CPT and with safety measurements of reactions to the product's administration. Lastly, the three-country, 39centre study design suggests that the present results can be extrapolated with confidence in populations in Western European countries in general.…”
Section: Discussionmentioning
confidence: 99%
“…TSS captured via CPT is shown to provide a reliable method for dose selection in AIT, 39 , 48 , 49 and successfully implemented in two earlier PQ Birch AIT studies, 40 and was applied to a population of 447 grass-allergic patients. The primary statistical analysis used to evaluate the dose response was recommended by the EMA, meeting the International Conference on Harmonisation E4 requirements 50 .…”
Section: Discussionmentioning
confidence: 99%
“…117 The conjunctival provocation test is a good predictor of SLIT outcome after only 4 weeks of treatment and can be used to identify candidates that will benefit from SLIT for an upcoming pollen season. 118 The levels of HDM-reactive T-cell subsets, ST2 + CD45RO + CD4 + and IL-5 + IL-13 + CD27 − CD161 + CD4 + , from PBMCs are reduced after 1 year of HDM SLIT and may be used as biomarkers of a positive therapeutic outcome. 119 Allergen manufacturing and quality aspects for allergen immunotherapy in Europe and the United States: An analysis from the EAACI AIT Guidelines Project 5 The international WAO/EAACI guideline for the management of hereditary angioedema -the 2017 revision and update 8 Allergen immunotherapy in people, dogs, cats and horses -differences, similarities and research needs 9 EAACI guidelines on allergen immunotherapy: Executive statement 10 EAACI guidelines on allergen immunotherapy: IgE-mediated food allergy 11 EAACI guidelines on allergen immunotherapy: Allergic rhinoconjunctivitis 15 Challenges in the implementation of the EAACI AIT guidelines: A situational analysis of current provision of allergen immunotherapy 16 Influenza burden, prevention, and treatment in asthma-A scoping review by the EAACI Influenza in asthma task force 17 EAACI guidelines on allergen immunotherapy: Hymenoptera venom allergy 18 Biomarkers for monitoring clinical efficacy of allergen immunotherapy for allergic rhinoconjunctivitis and allergic asthma: An EAACI position paper 123 Promoting and achieving excellence in the delivery of Integrated Allergy Care: the European Academy of Allergy & Clinical Immunology competencies for allied health professionals working in allergy 103 The urgent need for a harmonized severity scoring system for acute allergic reactions 127 Current practice of allergy diagnosis and the potential impact of regulation in Europe 128 EAACI/ENDA Position Paper: Diagnosis and management of hypersensitivity reactions to non-steroidal anti-inflammatory drugs (NSAIDs) in children and adolescents 129 Emerging roles of innate lymphoid cells in inflammatory diseases: Clinical implications 130 The roadmap for allergology in Europe: The subspecialty of allergology as "stop-over" on the way to a full specialty.…”
Section: Allerg En Immunother Apy ( Ait )mentioning
confidence: 99%
“…The clinical efficacy and positive safety profile of the SQ HDM SLIT‐tablets in patients older than 12 years are known and have been recently extended to include children (5‐11 years) with moderate‐to‐severe SQ HDM AR and with perennial AR . The conjunctival provocation test is a good predictor of SLIT outcome after only 4 weeks of treatment and can be used to identify candidates that will benefit from SLIT for an upcoming pollen season . The levels of HDM‐reactive T‐cell subsets, ST2 + CD45RO + CD4 + and IL‐5 + IL‐13 + CD27 − CD161 + CD4 + , from PBMCs are reduced after 1 year of HDM SLIT and may be used as biomarkers of a positive therapeutic outcome .…”
Section: Allergen Immunotherapy (Ait)mentioning
confidence: 99%